2015
DOI: 10.1103/physrevb.92.081304
|View full text |Cite
|
Sign up to set email alerts
|

Theory of interacting topological crystalline insulators

Abstract: We study the effect of electron interactions in topological crystalline insulators (TCIs) protected by mirror symmetry, which are realized in the SnTe material class and host multivalley Dirac fermion surface states. We find that interactions reduce the integer classification of noninteracting TCIs in three dimensions, indexed by the mirror Chern number, to a finite group Z 8 . In particular, we explicitly construct a microscopic interaction Hamiltonian to gap eight flavors of Dirac fermions on the TCI surface… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
130
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(133 citation statements)
references
References 51 publications
3
130
0
Order By: Relevance
“…Remarkably, it implies a field-induced dimensional reduction [22] that will strongly enhance correlations hence the advent of the (quasi-) 1D system without electron quasiparticle excitations. This connects to the long-lasting search or application of the Tomonaga-Luttinger liquid (TLL) physics [23], including semiconductor quantum wires [24,25], singlewalled carbon nanotubes [26,27], edge states in fractional quantum Hall states [28,29] and 2D topological insulators [30,31], and so on.Because of the large cyclotron gap, it is expected and confirmed that the Dirac/Weyl semimetals can be driven to the quantum limit at lower magnetic fields than semiconductors [20]. Due to the instability from electron correlations, one possibility is the gap-opening or dynamical mass generation [32] in the nominally massless semimetal as density waves are formed [33].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, it implies a field-induced dimensional reduction [22] that will strongly enhance correlations hence the advent of the (quasi-) 1D system without electron quasiparticle excitations. This connects to the long-lasting search or application of the Tomonaga-Luttinger liquid (TLL) physics [23], including semiconductor quantum wires [24,25], singlewalled carbon nanotubes [26,27], edge states in fractional quantum Hall states [28,29] and 2D topological insulators [30,31], and so on.Because of the large cyclotron gap, it is expected and confirmed that the Dirac/Weyl semimetals can be driven to the quantum limit at lower magnetic fields than semiconductors [20]. Due to the instability from electron correlations, one possibility is the gap-opening or dynamical mass generation [32] in the nominally massless semimetal as density waves are formed [33].…”
mentioning
confidence: 99%
“…Remarkably, it implies a field-induced dimensional reduction [22] that will strongly enhance correlations hence the advent of the (quasi-) 1D system without electron quasiparticle excitations. This connects to the long-lasting search or application of the Tomonaga-Luttinger liquid (TLL) physics [23], including semiconductor quantum wires [24,25], singlewalled carbon nanotubes [26,27], edge states in fractional quantum Hall states [28,29] and 2D topological insulators [30,31], and so on.…”
mentioning
confidence: 99%
“…Since then, there have been several works which discuss the breakdown of the noninteracting classification in the presence of interactions [14][15][16][17][18][19][20][21][22][23][24][25].…”
mentioning
confidence: 99%
“…An important question then is whether the nontrivial TCIs predicted by band theories are stable under interactions, or, more precisely, whether these band-theory-based nontrivial TCIs can be smoothly connected to a trivial insulator once strong interactions are switched on (still in the presence of the relevant symmetries). Very recently, the stability of various such TCIs under interactions has been considered and some of them are shown to be unstable, by studying the anomalous surface properties of the TCIs, studying certain dimensionally reduced versions of the TCIs, or studying the formal field theories of the TCIs [20][21][22][23][24][25][26][27][28][29][30][31]. However, an important and interesting question has remained unanswered: how to characterize nontrivial interacting TCIs directly by their bulk properties in a physical way?…”
Section: Introductionmentioning
confidence: 99%